The Alzheimer's Association international guidelines for handling of cerebrospinal fluid for routine clinical measurements of amyloid β and tau. Issue 9 (31st March 2021) - Hansson, Oskar; Batrla, Richard; Brix, Britta; Carrillo, Maria C.; Corradini, Veronika; Edelmayer, Rebecca M.; Esquivel, Rianne N.; Hall, Christina; Lawson, John; Bastard, Nathalie Le; Molinuevo, José Luis; Nisenbaum, Laura K.; et al.
Abstract: The core cerebrospinal fluid (CSF) Alzheimer's disease (AD) biomarkers amyloid beta (Aβ42 and Aβ40), total tau, and phosphorylated tau, have been extensively clinically validated, with very high diagnostic performance for AD, including the early phases of the disease. However, between‐center differences in pre‐analytical procedures may contribute to variability in measurements across laboratories. To resolve this issue, a workgroup was led by the Alzheimer's Association with experts from both academia and industry. The aim of the group was to develop a simplified and standardized pre‐analytical protocol for CSF collection and handling before analysis for routine clinical use, and ultimately to ensure high diagnostic performance and minimize patient misclassification rates. Widespread application of the protocol would help minimize variability in measurements, which would facilitate the implementation of unified cut‐off levels across laboratories, and foster the use of CSF biomarkers in AD diagnostics for the benefit of the patients.